2011
DOI: 10.1016/j.ajpath.2010.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Expression Profiles of p63 Variants during Urothelial Development and Bladder Cancer Progression

Abstract: The TP63 gene, a member of the TP53 tumor suppressor gene family, can be expressed as at least six isoforms due to alternative promoter use and alternative splicing. The lack of p63 isoform-specific antibodies has limited the analysis of the biological significance of p63. We report a novel set of well-defined antibodies to examine p63 isoforms in mouse and human urothelium during embryogenesis and tumor progression, respectively. We provide evidence that basal and intermediate urothelial cells express p63 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 36 publications
3
113
0
1
Order By: Relevance
“…Network analysis revealed significant TP63 expression that was associated with a high level of expression of the oncogenic Np63 isoform. It is likely that squamous/basal MIBCs expressing this isoform represent the lethal subset of p63-expressing advanced bladder cancers that were reported by others 169 . The relevance of p63 expression in poor prognosis UroB tumours remains unresolved, but the expression of different p63 isoforms in NMIBC and MIBC may account for this 169 .…”
Section: Beyond the 'Two Pathway' Modelmentioning
confidence: 74%
See 2 more Smart Citations
“…Network analysis revealed significant TP63 expression that was associated with a high level of expression of the oncogenic Np63 isoform. It is likely that squamous/basal MIBCs expressing this isoform represent the lethal subset of p63-expressing advanced bladder cancers that were reported by others 169 . The relevance of p63 expression in poor prognosis UroB tumours remains unresolved, but the expression of different p63 isoforms in NMIBC and MIBC may account for this 169 .…”
Section: Beyond the 'Two Pathway' Modelmentioning
confidence: 74%
“…It is likely that squamous/basal MIBCs expressing this isoform represent the lethal subset of p63-expressing advanced bladder cancers that were reported by others 169 . The relevance of p63 expression in poor prognosis UroB tumours remains unresolved, but the expression of different p63 isoforms in NMIBC and MIBC may account for this 169 . It is currently unclear whether analyses that have assessed MIBC only have revealed all biologically relevant heterogeneity as some data suggest that transcriptional subtypes are independent of conventional grade and stage groupings 191 .…”
Section: Beyond the 'Two Pathway' Modelmentioning
confidence: 74%
See 1 more Smart Citation
“…By contrast, transplants of p63 −/− urogenital sinus (UGS) revealed that luminal cells can form and regenerate in the absence of basal cells, hinting that the two cell types might represent independent cell lineages during development (12,16,25). Similarly, p63-deficient mouse urothelium contains umbrella-like cells in the absence of p63-positive basal/intermediate cells, suggesting that the cells are not related hierarchically (13,16,17). Because epithelial cell lineages in the developing bladder and prostate glands need to be further clarified, we generated knock-in mice expressing Cre recombinase (Cre) under control of the endogenous ΔNp63 promoter and performed a rigorous genetic lineage tracing analysis of ΔNp63-expressing cells in the developing caudal endoderm that gives rise to the prostate, bladder, and colorectal epithelia.…”
mentioning
confidence: 99%
“…Heterozygous p63 mutations underlie various human syndromes of ectodermal dysplasia, orofacial clefting, and limb malformation (15), and p63 KO mice show defects in limb, craniofacial, and epithelial development. These mice lack all stratified epithelia and their derivatives (i.e., mammary, lachrymal, and salivary glands), die at birth from dehydration, and have markedly abnormal prostate and bladder epithelia (12,13,16,17). Specific KO mice for the TA and the ΔNp63 isoforms reveal that these anomalies result from ΔNp63 absence (18,19).…”
mentioning
confidence: 99%